2009
DOI: 10.1124/mol.109.056531
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Selective Muscarinic Acetylcholine Receptor Subtype 1 Antagonist Reduces Seizures without Impairing Hippocampus-Dependent Learning

Abstract: Previous studies suggest that selective antagonists of specific subtypes of muscarinic acetylcholine receptors (mAChRs) may provide a novel approach for the treatment of certain central nervous system (CNS) disorders, including epileptic disorders, Parkinson's disease, and dystonia. Unfortunately, previously reported antagonists are not highly selective for specific mAChR subtypes, making it difficult to definitively establish the functional roles and therapeutic potential for individual subtypes of this recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
116
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 39 publications
8
116
1
1
Order By: Relevance
“…Selectively sensitizing M 1 with BQCA fully overcomes the amnestic effects of scopolamine in this model. These results contrast with data in M 1 Ϫ/Ϫ mice (27) and with an M 1 selective antagonist, VU0255035 (28). In the former study the M 1 Ϫ/Ϫ mice showed no deficit in CFC, and in the latter study VU0255035 reduced pilocarpine-induced seizures in rats, which requires M 1 (29), but did not interfere with CFC.…”
Section: Discussioncontrasting
confidence: 55%
“…Selectively sensitizing M 1 with BQCA fully overcomes the amnestic effects of scopolamine in this model. These results contrast with data in M 1 Ϫ/Ϫ mice (27) and with an M 1 selective antagonist, VU0255035 (28). In the former study the M 1 Ϫ/Ϫ mice showed no deficit in CFC, and in the latter study VU0255035 reduced pilocarpine-induced seizures in rats, which requires M 1 (29), but did not interfere with CFC.…”
Section: Discussioncontrasting
confidence: 55%
“…This notion is based on the fact that the M 1 -muscarinic receptor is the most highly expressed muscarinic receptor subtype in the cortex and hippocampus (12) and that pharmacological studies point to this receptor subtype as being the primary effector of cholinergic-mediated cognition (6,24,25). However, recent studies using M 1 -muscarinic receptor knockout mice (1) together with studies using more selective pharmacological tools (9,10) have suggested that the M 1 -muscarinic receptor does not mediate hippocampal cognition directly. Hence, our finding that the M 3 -muscarinic receptor is important in hippocampal-based learning and memory offers an alternative explanation for the positive effects of promoting cholinergic transmission in patients with a cognitive deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the M 1 -muscarinic receptor subtype has been proposed to be the subtype associated with acetylcholine-mediated cognition (6,7), recent gene-knockout experiments have cast doubt on the direct role of this receptor subtype in learning and memory (1,8). This has been reinforced by the discovery of a novel selective M 1 -muscarinic receptor antagonist that was effective in blocking M 1 -muscarinic receptor-mediated seizures in vivo but had no effect on hippocampal-based contextual fear conditioning (9). In addition, recent studies using an M 1 -muscarinic receptorpositive allosteric modulator, BQCA, have suggested that M 1 -muscarinic receptors can mediate learning and memory through an indirect mechanism by stimulating the prefrontal cortex (10).…”
mentioning
confidence: 85%
“…This 50 μM CCh-induced LTD was a saturated form of LTD in mouse PFC as higher concentration of CCh (100 μM) produced an LTD of similar magnitude (69.6 ± 5.0% baseline fEPSP; Figure 1f, white bar). Bath application of the orthosteric M 1 -selective antagonist (Sheffler et al, 2009) VU0255035 (10 μM) 10 min before and during CCh application led to a complete abolition of the CCh-induced mLTD (99.7 ± 11.7%), although the short-term depression in response remained unaffected (Figure 1d and f). Finally, application of 50 μM CCh in PFC slices prepared from M 1 -KO mice led to a short-term depression of baseline response but did not induce mLTD (96.0 ± 4.0%; Figure 1e and f).…”
Section: Muscarinic Ltd In Prefrontal Cortex Is Solely Mediated By Thmentioning
confidence: 99%